Gen Z Students at State Senior High School 3 Rembang Learn Financial Literacy and Invest Early - Roro Ayu Deby Citra Putri; Nita Afifah; Dian Anita Sari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to improve financial literacy among Generation Z students at SMA Negeri 3 Rembang, who generally possess limited knowledge regarding personal financial management and capital market investment. This community service program was motivated by national survey data indicating that Indonesia’s financial literacy rate remains relatively low, at only 38.03%, highlighting the urgent need for early financial education interventions. The program aimed to enhance students’ understanding, awareness, and basic competencies in managing finances and recognizing investment opportunities in the capital market. Materials and methods. The program was implemented using an educational and participatory approach through a series of structured activities, including Financial Literacy Counseling, Capital Market Investment Counseling, and a Capital Market School. The main activity was conducted in the form of a seminar-based training on November 7, 2023, involving 31 participants who were members of the student council (OSIS). The materials were delivered by competent speakers with expertise in finance and capital markets. Supporting methods included interactive discussions, visual learning media, and documentation through video recordings. Results. The program was successfully implemented as planned, resulting in the completion of financial literacy education, investment counseling, and Capital Market School activities. The findings indicate an improvement in students’ knowledge and understanding of financial management and capital market investment concepts. In addition, program documentation was disseminated through a YouTube video, and intellectual property rights (HKI) in the form of posters and activity videos are currently in the publication process. Conclusions. The community service program effectively increased financial literacy among participating students and demonstrated the importance of early financial education for Generation Z. Although some outputs are still in progress, the program showed positive educational impacts. It is recommended that future implementations involve a larger number of participants to broaden the program’s reach and maximize its long-term benefits.